CFD Simulation of Visco-Elastic Fluids in Vertical Flow Pipes - Nadiah Mohd Zaki, Nadiah (Universiti Teknologi Petronas, 2008)
Drilling fluids often used in drilling operations to remove cuttings from well, to cool and clean the bit, to control formation pressures, to maintain well bore stability and such. However, the rheological behavior of the fluid has been altered as additives are being introduced into them to maintain the shear-thinning property. Study of this type of fluid flow will enhance for better understanding on optimization of performance of drilling fluid, prevent any potential problems and keeping the operational cost minimal. The objectives of this project is to simulate and characterize the drilling fluid during pumping and transport of the cuttings from the bottom to the top of well in vertical flow pattern. Throughout the project, three different procedures carried out which are analytical, experimental and simulation method. In analytical method, two governing equations of motion, Continuity equation and Navier-Stokes equations were derived in accordance to the assumptions made. In experimental method, one model of basic drilling fluid and three models of drilling fluid with additives were tested to determine the rheological model. Results from experimental work then will be fed into the motion equations as well as into the simulation. In the end of the project, results from analytical and simulation will be compared and validated